Facile Synthesis of La-modified CeO2 with Microwave Method for CO2 Adsorption - Kuznetsova S. A. Svetlana Anatoljevna; Khalipova O. S. Olga Sergeevna; Malchik A. G. Aleksandra Gennadievna; Yu-Wen Chen (2024, 2024)
Title screen